Conceptual representation changes in Indonesian-English bilinguals - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2016)
This study investigated conceptual representations changes in bilinguals. Participants were Indonesian-English bilinguals (dominant in Indonesian, with different levels of English proficiency) and a control group composed of English-dominant bilinguals. All completed a gender decision task, in which participants decided whether English words referred to a male or female person or animal. In order to explore conceptual representations, we divided the words into gender-specific and gender-ambiguous words. Gender-specific words were words in which conceptual representations contained gender as a defining feature, in both English and Indonesian (e.g., uncle). In contrast, gender-ambiguous words were words in which gender was a defining feature in English but not a necessary feature in Indonesian (e.g., nephew and niece are both subsumed under the same word, keponakan, in Indonesian). The experiment was conducted exclusively in English. Indonesian-English bilinguals responded faster to gender-specific words than gender-ambiguous words, but the difference was smaller for the most proficient bilinguals. As expected, English-dominant speakers' response latencies were similar across these two types of words. The results suggest that English concepts are dynamic and that proficiency leads to native-like conceptual representations.